2020
DOI: 10.2147/ott.s216598
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Evaluation of the Safety and Efficacy of Trifluridine/Tipiracil in the Treatment of Advanced Gastric/Gastroesophageal Junction Adenocarcinoma: Evidence to Date</p>

Abstract: Trifluridine/tipiracil or TAS-102 (Taiho Oncology, Lonsurf ® , Princeton, NJ, USA) is a combination tablet of trifluridine, a thymidine-based nucleoside analog, and tipiracil, a thymidine phosphorylase inhibitor, in a 1:0.5 molar ratio. This drug was first approved for use in metastatic colorectal cancer patients. Recently, the U S Food and Drug Administration (FDA) and the European Medicines Agency (EMA) have granted approval of trifluridine/tipiracil for treatment of metastatic gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…DNA incorporation appears to be the main cytotoxic mechanism in the currently used clinical formulation of oral intermittent dosing [15]. In contrast, a better inhibition of thymidylate synthase is obtained with continuous In addition, trifluridine/tipiracil has been approved for the treatment of another difficult-to-treat gastrointestinal cancer, gastric and gastroesophageal junction adenocarcinoma, in patients that had previously received two or more standard of care lines of treatment [10]. The approval in this case was based on the multinational TAGS trial (NCT02500043) that showed prolongation in OS, PFS and the time to deterioration of ECOG performance status with trifluridine/tipiracil compared to placebo [11].…”
Section: Trifluridine/tipiracil Pharmacology and Mechanism Of Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA incorporation appears to be the main cytotoxic mechanism in the currently used clinical formulation of oral intermittent dosing [15]. In contrast, a better inhibition of thymidylate synthase is obtained with continuous In addition, trifluridine/tipiracil has been approved for the treatment of another difficult-to-treat gastrointestinal cancer, gastric and gastroesophageal junction adenocarcinoma, in patients that had previously received two or more standard of care lines of treatment [10]. The approval in this case was based on the multinational TAGS trial (NCT02500043) that showed prolongation in OS, PFS and the time to deterioration of ECOG performance status with trifluridine/tipiracil compared to placebo [11].…”
Section: Trifluridine/tipiracil Pharmacology and Mechanism Of Actionmentioning
confidence: 99%
“…After oral administration, trifluridine is catabolized on first pass in the liver by the enzyme thymidine phosphorylase (TP) to the inactive metabolite trifluorothymidine, which is then excreted by the kidneys [ 15 ]. Tipiracil is an inhibitor of TP that prevents first-pass catabolism of trifluridine, increasing its concentration and allowing for oral administration [ 10 ]. After reaching cancer cells, trifluridine is transported intracellularly by hENT1 to exert its antitumor effects [ 20 ].…”
Section: Trifluridine/tipiracil Pharmacology and Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation